2021
DOI: 10.3889/oamjms.2021.5578
|View full text |Cite
|
Sign up to set email alerts
|

Brachial Plexus Injury: Recent Diagnosis and Management

Abstract: Brachial plexus injury is known to be one of the most serious upper limb injuries, causes paralysis of the upper limbs and changes in activity of daily living, with the consequence disruption of activity of daily living, socio-economic problems, depression, and hopelessness. Management must be done properly. The evaluation and examination consist of detailed anamnesis on chronological events, complete physical examination, imaging studies, and electrophysiology study. Management can be done nonsurgically and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 67 publications
(146 reference statements)
0
12
0
Order By: Relevance
“…Pain and quality of life scores were also significantly better with a shorter delay. 1,2,19,29 These timeframes are the core of the treatment selection. In our study, nerve procedures were done in patients who come within 12 months after injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pain and quality of life scores were also significantly better with a shorter delay. 1,2,19,29 These timeframes are the core of the treatment selection. In our study, nerve procedures were done in patients who come within 12 months after injury.…”
Section: Discussionmentioning
confidence: 99%
“…Pain and quality of life scores were also significantly better with a shorter delay. 1 , 2 , 19 , 29 …”
Section: Discussionmentioning
confidence: 99%
“…The downward weight of the hand and distal forearm pushes the elbow and humerus upward and provides an efficient transmission of force by creating a fulcrum point at the level of the proximal forearm [16]. The shoulder cap fits snugly over the acromioclavicular joint region and applies the fulcrum to the proximal forearm from above, which is a better refinement of preventing shoulder subluxation and shoulder pain compared to slings and hemislings [2,16,17]. But the concern is unilaterally functional patients may have difficulty while donning and doffing, because it has more straps and adjustments.…”
Section: History Of Orthotic and Prosthetic Managements In Brachial P...mentioning
confidence: 99%
“…In adults, prevalence of brachial plexus injury shows 89% for male predominantly with a mean age of 29 years and median age of 25 years [1,2]. Traumatic injuries, such as motorcycle collisions, have the majority in epidemiology of BPI, approximately 44-70% [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Previous epidemiological studies in Soetomo General Academic Hospital Surabaya showed as much as 90% of BPI patients required a surgery because of getting motorcycle accidents [ 3 ]. Four methods of surgical armamentarium have been found to be result in best outcome: Nerve transfer, nerve grafting, external neurolysis, and free functional muscle transfer [ 4 ].…”
Section: Introductionmentioning
confidence: 99%